Analisis Dinamik pada Model Matematika SVEIBR dengan Kontrol Optimal Untuk Pengendalian Penyebaran Penyakit Kolera - Resmawan Resmawan; Sri Lestari Mahmud; Asriadi Asriadi; Agusyarif Rezka Nuha; Andi Agung; Sri Istiyarti Uswatun Chasanah (Universitas Negeri Gorontalo, 2023)
Cholera is an infectious disease that attacks the human digestive system and can cause death. This article discusses the research results related to the mathematical model of the spread of cholera in the form of an optimal control system by combining three control strategies: vaccination, quarantine, and environmental sanitation. Pontryagin's maximum principle is applied to obtain optimal conditions based on the control strategy applied. Referring to the optimal conditions set, the model was solved numerically using the Runge-Kutta Order 4 method to describe the theoretical results. The calculation results show that applying the three control strategies in controlling the spread of cholera positively impacts reducing the number of cases of infection so that disease transmission can be discontinued.